Properties of Functions in the Wiener Class BVp[a,b] for 0<p<1 - Yeli Niu; Heping Wang (Journal of Function Spaces)
We will investigate properties of functions in the Wiener class BVp[a,b] with 0<p<1. We prove that any function in BVp[a,b] (0<p<1) can be expressed as the difference of two increasing functions in BVp[a,b]. We also obtain the explicit form of functions in BVp[a,b] and show that their derivatives are equal to zero a.e. on [a,b].